Inhibiting Factors in the Distribution of Inheritance Rights for Girls According to East Sumba Customs in Wudipandak Village, East Sumba Regency - Apris Mbilinau; Sukardan Aloysius; Agustinus Hedewata (Indonesian Journal of Economic & Management Sciences, 2023)
One of the laws that is still valid in the process of inheritance is customary law which has its own norms that are separate from the applicable law. The inheritance procedure is prioritized by deliberation as the basis is the most important thing so that harmony and harmony in the family is maintained, inheritance has meaning and understanding as a method of transferring assets left by the heir to his heirs. Inheritance is the transfer of rights and obligations regarding the wealth of a deceased person to another who is still alive. So the problems can be formulated as follows: (1) What factors are the obstacles in dividing the inheritance of daughters according to East Sumba custom in the Wudipandak community, Tabundung District, East Sumba Regency (2) How to deal with the inhibiting factors in dividing the inheritance of daughters according to East Sumba custom in Wudipandak Village, Tabundung District, East Sumba Regency